Enhancing Digital Literacy for Ustadz/Ustadzah in Modern Islamic Boarding Schools at Banten Province through Sustainable Media Integration - Yayu Heryatun; Tri Ilma Septiana (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
Mastery of digital literacy is one of skills that must be possessed by modern humans in order to compete in the 21st century. However, the use of digital literacy as learning media and information acquisition has not been utilized optimally, included in the three fostered modern Islamic boarding schools (hereinafter pesantren). Therefore, this community service activity has main objective, namely to provide training for ustadz/ustadzah council in designing digital literacy programs that can be integrated in the learning process sustainably. To achieve the objective, this program used Community Based Participatory Research method by involving various parties such as residents of pesantren (kiai, ustadz/ustadzah, librarian and santri), community representatives (literacy activists), and lecturers (universities). Finally, this program has positive implications. This is reflected in: (1) the integration of digital literacy media into the learning process sustainably; (2) the development of a literacy culture; (3) the realization of a literate pesantren environment.